The youth online training and employment system: Study protocol for a randomized controlled trial of an online vocational intervention for young people with mental ill health. Issue 6 (10th January 2021) - Simmons, Magenta B.; Nicholas, Jennifer; Chinnery, Gina; O'Sullivan, Shaunagh; D'Alfonso, Simon; Bendall, Sarah; Cagliarini, Daniela; Hamilton, Matthew; Gleeson, John; Killackey, Eóin; Alvarez‐Jimenez, Mario
Abstract: Aim: People diagnosed with mental disorders experience higher rates of unemployment than those without. Career adaptability, defined as the ability to respond flexibly and make informed career decisions in work and throughout career transitions, is becoming increasingly important as the nature of work changes rapidly. Early vocational intervention may ameliorate poor education and employment outcomes experienced by young people with mental ill‐health and promote transferable skills and adaptability. Online‐based career support allows for ongoing access throughout different career stages. The current study combines mental health‐informed digital career and peer motivation, to create a Youth Online Training and Employment System (YOTES) that supports young people with mental ill‐health obtain and remain in education or employment. Methods: This study is an unblinded randomized controlled trial for young people with mental ill‐health, aged 16–25, who are seeking vocational support. Participants will be randomized to receive either YOTES, a moderated, online intervention with vocational, social, and peer motivation, or a control intervention, the headspace Digital Work and Study Service. Both groups will have access to in‐person career support if seeking employment. The primary outcome will be career adaptability compared between the YOTES and control groups at 6‐months post baseline. Secondary outcomes include number of hours worked in the past 7 days, hope, career confidence, psychological distress and health economic outcomes at 6‐ and 12‐months post baseline. Conclusion: Results will demonstrate whether an online career intervention moderated by career practitioners with peer motivation can result in improved career adaptability in young people with mental ill‐health.